Audit 4.0: Determinants and Implications of Audit Opinions in the AI Era - Latjompo, Sri Mulyani; Anggraeni, Ayu Dhina; Namra, Namra; Amiruddin, Amiruddin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the factors influencing the implementation of Audit 4.0 and its implications for the formation of audit opinions in the era of artificial intelligence (AI). Audit 4.0 marks a significant transformation in the audit profession through the application of digital technologies such as artificial intelligence (AI), big data analytics, robotic process automation (RPA), and cloud computing, which can improve the efficiency, accuracy, and precision of auditor analysis. This study uses a systematic literature review method by examining scientific articles published between 2018 and 2025 from the Scopus, ScienceDirect, and Google Scholar databases. The results show that the success of Audit 4.0 implementation is determined by three main factors: auditor digital competence, technological readiness, and organizational support. The integration of digital technology has been shown to strengthen the quality of audit evidence and the objectivity of the resulting opinion, while accelerating the audit process. However, the findings also indicate that excessive reliance on automated systems can reduce the application of professional judgment and create the risk of automation bias. Thus, the success of Audit 4.0 depends not only on technological sophistication but also on the auditor's ability to maintain a balance between the use of technology and their professional responsibilities. This research is expected to provide theoretical contributions to the development of literature on audit digitalization and serve as a basis for audit institutions in formulating strategic policies to improve audit quality in the era of digital transformation